Are House Prices Driven by Capital Flows? Evidence from Singapore - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2016)
This paper investigates whether real house price appreciations can be attributed to the surge in real capital inflows into Singapore. We proxy capital flows by using the amount of foreign direct investments (FDI) to real estate capturing the foreign purchases of property in Singapore which we deflate by the private residential property price index. Notwithstanding the absence of a cointegrating relationship, our results support the hypothesis that lagged short term fluctuations in capital inflows are positively associated with the growth rates of house prices over the last decade. We also provide evidence that macroprudential measures implemented by Singapore reduced the impact of capital inflows on house price appreciation by more than half, suggesting the effectiveness of such market cooling measures in weakening the credit growth channel.